THE EFFECT OF LEADERSHIP, CULTURAL WORK AND MOTIVATION ON PERFORMANCE OF FIELD AGRICULTURAL EXTENSION WORKERS (Study at Agriculture Service of Bondowoso Regency) - Kusmiati Kusmiati; Bagus P Yudha; Zainollah Zainollah (MBA - Journal of Management and Business Aplication, 2018)
This research was conducted with the purpose of knowing and analyzing the leadership, cultural work and motivation which have a significant effect on the Performance of Field Agricultural Extension in Agriculture Service of Bondowoso regency partially and simultaneously and to know the dominant variable influencing the performance of Field Agricultural Extension in Agriculture Service of Bondowoso regency. The object of this research is Field Agricultural Extension in Agriculture Service of Bondowoso regency which is 69 people. This research uses quantitative research. As an independent variable namely leadership (X1), work culture (X2) and motivation (X3) and the dependent variable is Performance (Y). Data analysis used is validity and reliability test, multiple regression assumption test, and multiple linear regression analysis. The results showed that leadership, work culture had a significant partial effect while motivation did not have a significant partial effect, leadership, work culture and motivation simultaneously had a significant effect on the performance of field agriculture instructors. With the largest leadership regression coefficient, it can be concluded that the leadership variable has a dominant influence on the performance of field agricultural extension workers. The result of the determination coefficient (R2) is 0.662 (66.2%). So the performance of field agricultural extension workers in the Agriculture Service of Bondowoso regency is influenced by the three independent variables at 66.2% while the remaining 33.8% is influenced by other variables outside the research Keywords: Leadership, Work Culture, Motivation, Performance